To Wear or Not to Wear: Analysis of Individuals’ Tendency to Wear Masks during the COVID-19 Pandemic in China - Min Wang (MDPI AG, 2021)
During the COVID-19 pandemic, the percentage of Chinese people wearing masks was very high, as was the acceptance and initiative toward mask wearing. This national action merits our exploration of the psychological reasons as well as the general social and environmental factors behind this behavior. In this article, we integrated the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) as well as Health Belief Model and set up a mask acceptance model. We used a questionnaire survey and received 337 valid questionnaires. The results indicate that social influence, perceived susceptibility to COVID-19, perceived hedonic benefit (appearance enhancement), and a perceived barrier (hindrance to communication) exert significant influences on the willingness to wear masks. Meanwhile, social influence plays an intermediary role between interdependent self-construal and intention to wear a mask. We hope to reveal the micro psychological reasons for the national action and reflect on the cultural characteristics of Chinese people in the special context of the COVID-19 pandemic.